Phytotherapy used in the Treatment of Oral Diseases: a Cross-Sectional Study in Indigenous Population - Silva, Daniel Dornelles da; Calcia, Thayanne Brasil Barbosa; Daroit, Natalia Batista (ARCHIVES OF HEALTH INVESTIGATION, 2023)
Phytotherapy studies the pharmacological effects of plants with the therapeutic purpose of preventing, curing, or minimizing disease symptoms. The use of plants by indigenous people to treat health conditions has been documented since ancient times. This study aimed to report an indigenous community’s herbal medicines for oral diseases. An online questionnaire was administered, in which the participant indicated the type of plant and the part used, the preparation form, the administration route, and the dental condition. Subsequently, a descriptive analysis was performed. Most study participants were women (n=72, 62.1%). Peppermint tea (21.5%) was the most used substance for mouthwash and halitosis (42.2%). The bark of Açoita (34.5%) and Aroeira (31.9%) were the most frequently used to treat dental pain. Regarding gingival diseases, most responded that they used Guamirim (64.5%). Only mallow tea was reported to treat canker sores (81%). However, for herpetic lesions, participants reported the application of clay in a wasp nest (Polistes canada), an insect present at the site (55.2%). Oral inflammation had the lowest reported use of herbal medicine, with Marcela tea being the most frequently used (10.3%). Finally, fern roots were the most frequently used for infections (32 %). In conclusion, indigenous people widely use phytotherapeutics to treat oral diseases. Learning about the use of herbal medicines in indigenous communities may increase the clinical applicability of these plants in the dental field and, in the future, serve as a basis for developing new drugs.